PANTANGAN MANDI MENGGUNAKAN SABUN DAN SHAMPO DI AIR TERJUN SEDUDO DALAM PERSPEKTIF ISLAM - Anisa Zakia Rahma; Bagus Wahyu Setyawan (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2024)
Indonesia has a high culture, one of which is Nganjuk district, which from a cultural aspect has quite rich diversity. One of them is the siraman tradition which is usually carried out at Sedudo Waterfall. The various myths and stories that color Sedudo Waterfall about its place containing mystical values have caused it to continue to develop into a tradition to this day. Tourist attractions that are known for their mystique are certainly inseparable from the myths that have developed. With this myth, the Sedudo Waterfall tourist attraction has a number of restrictions that visitors must pay attention to. One of these taboos is that you are prohibited from bathing using soap and shampoo because it will bring bad luck to those who do so.